Prognostic significance of KRAS, NRAS, BRAF, and PIK3CA mutations in stage II/III colorectal cancer: A retrospective study and meta-analysis. - Di Kang; Jing Li; Yangyang Li; Jingquan Xu; Jianlei Yang; Zili Zhang (PLoS ONE)
The prognostic significance of KRAS and BRAF mutations is well-established in metastatic colorectal cancer (CRC) but remains uncertain in early-stage tumors. This study retrospectively analyzed 47 stage II/III CRC patients undergoing curative surgery to assess the association of mutations in KRAS, NRAS, BRAF, and PIK3CA with overall survival (OS) and disease-free survival (DFS). Additionally, a meta-analysis was conducted to validate the prognostic relevance of these gene mutations. We included post hoc analyses of phase III randomized controlled trials (RCTs) in stage II/III patients receiving adjuvant therapy after curative resection in the meta-analysis. Pooled hazard ratio (HR) and 95% confidence interval (CI) was calculated using a random-effect model in the overall population, stratified subgroups adjusted for microsatellite instability (MSI) status, and within MSI-high (MSI-H) and microsatellite-stable (MSS) populations. In the retrospective cohort, mutations in KRAS, NRAS, BRAF, and PIK3CA were identified in 29.8%, 4.3%, 8.5%, and 14.9% of patients, respectively. No significant association between individual genes and survival was observed. However, in MSS patients, concurrent mutations were significantly associated with shorter OS and DFS (log-rank test, P < 0.05). The meta-analysis incorporated 13 eligible studies, including 15,034 patients. Pooled analyses revealed that KRAS and BRAF mutations were significantly linked to poor OS (KRAS: HR = 1.25, 95%CI: 1.06-1.47, P = 0.008; BRAF: HR = 1.43, 95%CI: 1.26-1.63, P < 0.001) and DFS (KRAS: HR = 1.36, 95%CI: 1.21-1.53, P < 0.001; BRAF: HR = 1.21, 95%CI: 1.02-1.44, P = 0.032). The prognostic impact of BRAF mutation increased with MSI adjustment compared those without MSI adjustment. In MSS tumors, KRAS-mutant patients demonstrated significantly shorter DFS (HR = 1.63, 95%CI: 1.25-2.13, P < 0.001), while BRAF-mutant patients exhibited reduced OS (HR = 1.53, 95%CI: 1.24-1.89, P < 0.001) and DFS (HR = 1.72, 95%CI: 1.20-2.46, P = 0.003) compared to wildtype patients. Conversely, no significant survival differences were found between mutant and wildtype patients in the MSI-H population. Although PIK3CA mutation was nominally associated with OS (HR = 0.86, 95%CI: 0.75-1.00, P = 0.046), the pooled result lacked robustness. In conclusion, KRAS and BRAF mutations had a negative prognostic impact on MSS stage II/III CRC patients receiving adjuvant therapy following curative resection. These patients may benefit from more effective adjuvant treatment strategies.